Drawings as a Component of Triangulated Assessment - Charlotte A. Otto; Susan A. Everett; Gail R. Luera; Christopher F.J. Burke (Networks: An Online Journal for Teacher Research, 2013)
Action research (AR) in an educational setting as described by Tillotson (2000) is an approach to “classroom-based problems” or “specific school issues” (p. 31). His process involves identification of the issue or problem, development and implementation of an action plan, gathering and interpreting data, sharing the results within the community, and “action planning” as a cyclical endeavor (Tillotson, 2000, p. 32). AR is utilized as a key component of developing pre-service teachers in the University of Michigan-Dearborn certification program. Illustrating the five components of Tillotson’s approach, pre-service elementary teachers develop and analyze pre-assessments of K-8 student knowledge about a specific science topic to identify prior student understanding; they create and teach two lessons to provide applicable scientific content, post-assess to determine the impact of their teaching and write a research journal style report describing their project. The AR assignment is more structured than a typical action research project in order to support the pre-service teachers, many whom have never conducted a literature review, created assessments linked to research, or completed an AR project (Luera & Otto, 2005).